Genome Sequence of the Bacteriocin-Producing Strain Lactococcus garvieae DCC43 - Gabrielsen, Christina (American Society for Microbiology, 2012)
This work describes the draft genome sequence of Lactococcus garvieae DCC43. The 2.2-Mb draft genome contains 2,227 predicted protein-coding genes, among which is a region encoding the bacteriocin garvicin ML. No antibiotic resistance genes or capsule-related virulence genes were identified. Two plasmid replication regions indicate that this strain likely contains plasmids. Comparative genomics suggests that this strain displays a high degree of sequence variation from the previously sequenced L. garvieae strains.